Intrinsic Motivation Mediates the Influence of Affective Commitment on OCB in Kertamulya Bumdes in West Bandung District - Bagja, Hafied Noor; Rachmat, Radhi Abdul Halim; Tantular R, Yoga (International Publisher, 2024)
Appropriate organizational governance will support fair management of BUM Desa so as to provide satisfaction for village communities. Fair organizational management can improve managerial performance through implementing decisions that represent interested individuals . Participation and contribution of village communities is important in managing BUM Desa, so BUM Desa really needs to implement procedural justice in the governance of its organization. This research aims to find out whether intrinsic motivation mediates the influence of affective commitment on OCB in BUMDes Kertamulya in West Bandung Regency. The data analysis method used is descriptive verification method with multiple regression linear analysis and Sobel test. Findings prove that Commitment affective influence motivation intrinsic but influence OCB. Study shows that internal motivation mediates the influence of individual characteristics on OCB. this finding can provide managerial considerations about antecedents of OCB.